SIMULASI SISTEM MONITORING DAYA LISTRIK TEGANGAN RENDAH MENGGUNAKAN KABEL SERIAL - Sri Ipnuwati (LPPM STMIK Pringsewu, 2014)
One of the problems faced by business today, especially businesses engaged in the electricity industry is the problem. Where electricity is used for the production process should not suddenly drop out so that the activities have hampered production. then one solution is to conduct monitoring of the loads of power used by electrical power is available so it will not happen Over Blast, a condition in which the cost of power used exceeds a predetermined limit. The simulation was made of the above problems Monitoring System Using Low Voltage Power Cables Serial. This system is used on two computers that are connected using a serial cable via COM 1 and used a method of data transmission is asynchronous data transmission method using a data transfer speed of 9600 bits per second. Research carried out resulted in an application that can monitor down - rising power.